Three-dimensional printing of clinical scale and personalized calcium phosphate scaffolds for alveolar bone reconstruction. Issue 3 (March 2022) - Anderson, Margaret; Dubey, Nileshkumar; Bogie, Kath; Cao, Chen; Li, Junying; Lerchbacker, Joseph; Mendonça, Gustavo; Kauffmann, Frederic; Bottino, Marco C.; Kaigler, Darnell
Abstract: Objective: Alveolar bone defects can be highly variable in their morphology and, as the defect size increases, they become more challenging to treat with currently available therapeutics and biomaterials. This investigation sought to devise a protocol for fabricating customized clinical scale and patient-specific, bioceramic scaffolds for reconstruction of large alveolar bone defects. Methods: Two types of calcium phosphate (CaP)-based bioceramic scaffolds (alginate/β-TCP and hydroxyapatite/α-TCP, hereafter referred to as hybrid CaP and Osteoink™, respectively) were designed, 3D printed, and their biocompatibility with alveolar bone marrow stem cells and mechanical properties were determined. Following scaffold optimization, a workflow was developed to use cone beam computed tomographic (CBCT) imaging to design and 3D print, defect-specific bioceramic scaffolds for clinical-scale bone defects. Results: Osteoink™ scaffolds had the highest compressive strength when compared to hybrid CaP with different infill orientation. In cell culture medium, hybrid CaP degradation resulted in decreased pH (6.3) and toxicity to stem cells; however, OsteoInk™ scaffolds maintained a stable pH (7.2) in culture and passed the ISO standard for cytotoxicity. Finally, a clinically feasible laboratory workflow was developed and evaluated using CBCT imaging to engineer customized and defect-specific CaP scaffolds using OsteoInk™. It was determined that printed scaffolds had a high degree of accuracy to fit the respective clinical defects for which they were designed (0.27 mm morphological deviation of printed scaffolds from digital design). Significance: From patient to patient, large alveolar bone defects are difficult to treat due to high variability in their complex morphologies and architecture. Our findings shows that Osteoink™ is a biocompatible material for 3D printing of clinically acceptable, patient-specific scaffolds with precision-fit for use in alveolar bone reconstructive procedures. Collectively, emerging digital technologies including CBCT imaging, 3D surgical planning, and (bio)printing can be integrated to address this unmet clinical challenge.